Can This Time Be Different? Policy Options in Times of Rising Debt - Kose, M. Ayhan (World Bank, Washington, DC, 2020)
Episodes of debt accumulation have been a recurrent feature of the global economy over the past fifty years. Since 2010, emerging and developing economies have experienced another wave of historically large and rapid debt accumulation. Similar past debt buildups have often ended in widespread financial crises in these economies. This paper examines the factors that are likely to determine the outcome of the most recent debt wave, and considers policy options to help reduce the likelihood that it ends again in widespread crises. It reports two main results. First, the rapid increase in debt has made emerging and developing economies more vulnerable to shifts in market sentiment, notwithstanding historically low global interest rates. Second, policy options are available to lower the likelihood of financial crises, and to help manage the adverse impacts of crises when they do occur. These include sound debt management, strong monetary and fiscal frameworks, and robust bank supervision and regulation. The post-crisis debt buildup has coincided with a period of subdued growth as well as the emergence of non-traditional creditors. As a result, policy priorities also need to ensure that debt is spent on productive purposes to improve growth prospects and that all debt-related transactions are transparently reported.